Schiff Base Metal Complexes as Anticancer Agents - Sridevi, G.; Antony, S. Arul; Angayarkani, R. (Asian Journal of Chemistry, 2019)
Cutting-edge practices in bioinorganic chemistry are pivotal for enhancing the layout of compounds to lessen poisonous facet effect and recognize their mechanism of action. A powerful anticancer agent should own inherent, inhibitory property and also delivery, dosage and residence time in vivo. Organic function and conformation of mutated gene may be altered by way of binding of metal ions. Upswing of activities counting on the structural data, intending in enhancing and growing different forms of metal based compounds, continuous seek of extra metal based compounds have been synthesized via revamping the prevailing chemical shape via ligand substitution. The prevailing paper addresses the trendy development in the design of novel antitumor agents primarily based on transition metal complex via highlighting the near dating among their structural alternatives and cytotoxic ability.